Analytical model of skip motion taking into account influence of head and balancing ropes - Zhuravkov, Mikhail A.; Savchuk, Vladimir P.; Nikolaitchik, Michael A. (Journal of the Belarusian State University. Mathematics and Informatics, 2021)
The article describes an analytical model of mine skip dynamics taking into account the presence of the head and balancing ropes and the existing curvilinearity of the guides. Expressions for the forces acting on the skip from the side of the guides have been constructed. It is shown, that the frequencies of natural vibrations of skip depend on the vertical acceleration and the distance traveled during its lifting. A graph (diagram) of skips vertical speed which observance does not lead to the appearance of skips vertical vibrations due to elasticity of the ropes is developed. An algorithm for finding the forces principal vector and the forces principal moment acting on the skip based on the reading of three accelerometers recording horizontal accelerations of skip during its movement is presented.